Serum PM20D1 levels are associated with nutritional status and inflammatory factors in gastric cancer patients undergoing early enteral nutrition - Jin Zhengyu; Chen Yuning (Open Medicine)
Early nutritional support holds paramount importance for postoperative gastric cancer (GC) patients. Peptidase M20 domain containing 1 (PM20D1) is a secretory enzyme associated with glucose and lipid metabolism. However, there is a dearth of clinical studies delving into the connection between PM20D1, lipid metabolism, and inflammatory factors in GC patients who have received enteral nutrition (EN). This research aimed to investigate the serum levels of PM20D1 in GC patients following early EN and their potential associations with lipid metabolism, nutritional markers, and inflammatory factors.